Russian stage design 1880-1930 - Bowlt, John E.; Lobanov-Rostovsky, Nina; Lobanov-Rostovsky, Nikita D. (Woodbridge : Antique Collectors' Club, 2012)
Charts one of the most important interludes within the Russian cultural Renaissance of the early 20th Century.
2. Encyclopedia of Russian stage design
boek
Keywords: Rusland